Perceptions of caregivers about surgical children's thirst - Mariana Campos Campana; Ligia Fahl Fonseca; Dolores Ferreira de Melo Lopes; Pamela Rafaela Martins (Universidade Federal do Ceará, 2015)
Objective: to understand how caregivers experience surgical children's fasting and how they realize their thirst in the perioperative period. Method: descriptive study of qualitative nature, carried out with 15 caregivers of children between 1 and 12 years old after surgery in a teaching hospital. For analysis, the Collective Subject Discourse method was used. Results: four thematic units emerged: surgical children in the presence of fasting and thirst; realizing thirst in surgical children; experiencing and facing the period of fasting and thirst with children; realizing the action of the health team in the presence of children's thirst. For families, the experience of fasting is permeated with feelings like helplessness and distress. The presence of thirst, detected by self-report and physical signs, exacerbates their suffering. Conclusion: thirst management alleviates the suffering of children and families. It is therefore necessary to develop strategies for children's thirst management.